Evaluating the Impact of Openness to Experience on Digital Transaction Usage: A Quantile Regression Analysis - Putri, Fildzah Rudyah; Mahdiyah, Mahdiyah; Madani, Faisal; Dahlia, Mutiara (LPPM Universitas Negeri Jakarta, 2024)
Digital wallets have become an important part of financial transactions, especially among college students. This study aims to analyze the influence of the personality dimension of Openness to Experience on the use of digital wallets using quantile regression analysis. This approach allows exploration of variations in the influence of Openness to Experience at low, medium, and high levels of transaction intensity. Data were taken from 212 students of Jakarta State University measured through an online survey. The results showed that Openness to Experience had a positive effect on the use of digital wallets, with a stronger effect on the upper quantile. This suggests that individuals with high levels of openness tend to be more enthusiastic in adopting new technologies and exploring digital wallet features.